Plutarch and the Persica - Almagor, Eran (Edinburgh University Press, 2018)
This book addresses two historical mysteries. The first is the content and character of the fourth century BCE Greek works called the Persica. The second is the method of work of the second century CE biographer Plutarch of Chaeronea who used these works to compose his biographies.
Title from publisher's bibliographic system (viewed on 12 Nov 2020)
Keywords: Plutarch; Ctesias; Dinon; Heraclides; Plutarchus; Dinon; Heraclides; Persica; Aratus et Artaxerxes; Fragments; Rezeption